INFORMATION AND COMMUNICATION TECHNOLOGIES AND STUDENTS - MEIER, Miroslav (Trends in education, 2015)
The paper presents the results of the investigation, which dealt with ways of using information and communication technologies of students in combined study and of students in full-time study. Described are the differences between the groups of students.
Keywords: information and communication technologies; Internet; students; studies.